LC-MS/MS-Based Method for the Multiplex Detection of 24 Fentanyl Analogues and Metabolites in Whole Blood at Sub ng mL(–1) Concentrations - Strayer, Kraig E. (ACS Omega, 2018)
[Image: see text] The United States and numerous other countries worldwide are currently experiencing a public health crisis due to the abuse of illicitly manufactured fentanyl (IMF) and its analogues. This manuscript describes the development of a liquid chromatography-tandem mass spectrometry-based method for the multiplex detection of N = 24 IMF analogues and metabolites in whole blood at concentrations as low as 0.1–0.5 ng mL(–1). These available IMFs were fentanyl, norfentanyl, furanyl norfentanyl, remifentanil acid, butyryl norfentanyl, remifentanil, acetyl fentanyl, alfentanil, AH-7921, U-47700, acetyl fentanyl 4-methylphenethyl, acrylfentanyl, para-methoxyfentanyl, despropionyl fentanyl (4-ANPP), furanyl fentanyl, despropionyl para-fluorofentanyl, carfentanil, (±)-cis-3-methyl fentanyl, butyryl fentanyl, isobutyryl fentanyl, sufentanil, valeryl fentanyl, para-fluorobutyryl fentanyl, and para-fluoroisobutyryl fentanyl. Most IMF analogues (N = 22) could be easily distinguished from one another; the isomeric forms butyryl/isobutyryl fentanyl and para-fluorobutyryl/para-fluoroisobutyryl fentanyl could not be differentiated. N = 13 of these IMF analogues were quantified for illustrative purposes, and their forensic quality control standards were also validated for limit of detection (0.017–0.056 ng mL(–1)), limit of quantitation (0.100–0.500 ng mL(–1)), selectivity/sensitivity, ionization suppression/enhancement (87–118%), process efficiency (60–95%), recovery (64–97%), bias (<20%), and precision (>80%). This flexible, time- and cost-efficient method was successfully implemented at the Montgomery County Coroner’s Office/Miami Valley Regional Crime Laboratory in Dayton, Ohio, where it aided in the analysis of N = 725 postmortem blood samples collected from February 2015 to November 2016.